Successful unrelated umbilical cord blood transplantation for class 3 β‐thalassemia major using a reduced‐toxicity regimen. (16th December 2013) - Soni, Sandeep; Breslin, Nancy; Cheerva, Alexandra
Abstract Unrelated umbilical CB transplant for class 3 β‐thalassemia major is associated with an increased risk of mortality and non‐engraftment. We describe two patients who underwent successful unrelated umbilical CB transplant using a novel reduced‐toxicity preparative regimen. This regimen may be sufficiently immunosuppressive and myeloablative to ensure engraftment with reduced risks of toxicity and mortality. Close monitoring of HHV‐6 viral load is advised for patients undergoing transplant with this regimen.